Mathematics Teacher’s Autonomy in Students’ Performance - Gnawali, Yagya Prasad (Ganeshman Darpan, 2023)
This study aims to investigate the perceptions of mathematics teachers’ autonomy in students’ performance. I applied quantitative research design, and positivist paradigm. In Kathmandu district’s 40 public secondary schools, 80 respondents in the basic level teachers, 40 male and 40 females-were randomly selected for the sample. Data collection was carried out using a self-created questionnaire that had 50 statements and five Likert-type response alternatives. The self-developed questionnaire’s validity was verified by the opinions of experts, and reliability was established Cronbach’s alpha, 0 .89. I prepared five factors according to loading components. According to research, teacher’s autonomous teaching makes high performance of students in mathematics classroom practices.